2023
DOI: 10.31284/j.jmesi.2023.v3i1.4477
|View full text |Cite
|
Sign up to set email alerts
|

Wavy Leading Edge (WLE) Influence on a Rectangular Wing Using an Unsteady Analysis Approach

Abstract: A rectangular wing with Wavy Leading Edge (WLE) effect was investigated experimentally and numerically. This research was carried out with the NACA 0018 profile. The morphology of humpback whale flippers, which are blunt and rounded in a specific pattern, inspired the design of the WLE. The rectangular wing was explored in pitching motion with a reduced frequency of k = 0.25 and varied aspect ratios. Multiple aspect ratios (AR) of the rectangular wing have been evaluated to determine the best wing aspect ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Miklosovic et al [18], conducted experimental trials on sinusoidal leading-edge wings, and their findings revealed that wings with larger amplitudes exhibited a more gradual stall pattern, attributed to stalls occurring later in the regions behind the peaks compared to those behind the troughs. Other scholars validated this through an experimental and numerical investigation of a rectangular wing incorporating the Wavy Leading Edge effect, demonstrating improved lift force during pitching motion with minimized stall [19][20][21], suggesting potential applications in wind turbines [22][23][24]. The experimental investigation performed by N. Karthikeyan et al [25,26] examined the impact of wavy leading edges, revealing tubercles' effectiveness in maintaining attached flow and reducing recirculating zones, although their influence on separation point variability and wake width post-stall requires further exploration.…”
Section: Introduction 1backgroundmentioning
confidence: 85%
“…Miklosovic et al [18], conducted experimental trials on sinusoidal leading-edge wings, and their findings revealed that wings with larger amplitudes exhibited a more gradual stall pattern, attributed to stalls occurring later in the regions behind the peaks compared to those behind the troughs. Other scholars validated this through an experimental and numerical investigation of a rectangular wing incorporating the Wavy Leading Edge effect, demonstrating improved lift force during pitching motion with minimized stall [19][20][21], suggesting potential applications in wind turbines [22][23][24]. The experimental investigation performed by N. Karthikeyan et al [25,26] examined the impact of wavy leading edges, revealing tubercles' effectiveness in maintaining attached flow and reducing recirculating zones, although their influence on separation point variability and wake width post-stall requires further exploration.…”
Section: Introduction 1backgroundmentioning
confidence: 85%